2007
DOI: 10.1038/oby.2007.312
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Lactose on Long‐term High‐fat‐diet‐induced Obesity in Rats

Abstract: GOSEKI-SONE, MASAE, RIEKO MARUYAMA, NATSUKO SOGABE, AND TAKAYUKI HOSOI. Effects of dietary lactose on long-term high-fat-diet-induced obesity in rats. Obesity. 2007;15:2605-2613. Objective: In this study, we examined the effects of lactose on long-term high-fat-diet-induced obesity in rats. Research Methods and Procedures:A total of 112 Sprague-Dawley strain female rats (6 weeks old) were divided into four groups: a basic control diet group (Cont), 10% lactose diet group (Lac), high-fat diet group (Fat), and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 49 publications
4
17
0
Order By: Relevance
“…However, the effects of body mass on the skeleton remain controversial although well documented in obese subjects in previous studies [35,36]. Some studies have shown that obese subjects have weaker bone to bear their over-weight body mass compared to normal counterparts in both humans and animals [37,38]. In our study, after adjusting for body mass (unpublished data), no significant differences in bone traits between the obese and normal weight mice were found.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of body mass on the skeleton remain controversial although well documented in obese subjects in previous studies [35,36]. Some studies have shown that obese subjects have weaker bone to bear their over-weight body mass compared to normal counterparts in both humans and animals [37,38]. In our study, after adjusting for body mass (unpublished data), no significant differences in bone traits between the obese and normal weight mice were found.…”
Section: Discussionmentioning
confidence: 99%
“…Morphometric parameters of the distal metaphysis of the femur were measured as described previously 63 , with the following parameters calculated: bone volume (BV), tissue volume (TV), bone mineral density (BMD), cortical mineral density (CMD), cortical mineral volume (CMV), and bone volume fraction (BV/TV).…”
Section: Methodsmentioning
confidence: 99%
“…After acclimatization, half the rats were fed a standard chow diet (3 kcal/g, 14 % calories from fat, 32 % calories from protein, 54 % calories from carbohydrate; 8604 Teklad rodent diet, Harlan) and the other half fed a high-fat diet (5.25 kcal/g, 60 % calories from fat, 20 % calories from protein, 20 % calories from carbohydrate; Open Source Diets D12492) for 18 weeks. Eighteen weeks was chosen based on the different lengths of time used in previous studies [2, 15, 17]. Each rat was singly caged and had unrestricted access to food and water.…”
Section: Methodsmentioning
confidence: 99%